Analisis Semiotika Roland Barthes Pada Lagu "Sun Goes Down" Karya Lil Nas X - Luthfiyah, Finna Nazmi; Sabri, Sabri (Tuturlogi: Journal of Southeast Asian Communication, 2023)
This research aims to explain the meaning of denotation, connotation and myth contained in the lyrics of the song "Sun Goes Down" by Lil Nas The method used in this research is descriptive qualitative. The technique used in this research uses data analysis techniques by analyzing the verses in the song "Sun Goes Down" by Lil Nas X contains an expression of feelings of despair where he is no longer strong enough to continue living. The next meaning is connotation, the connotation meaning contained in the song is a motivation or encouragement that is obtained to continue living, where we must not just give up on the situation. The final meaning is myth, the meaning of myth contained in the song is a statement "Strangers make you feel so loved, you know?" which means that someone we don't know in real life can actually make us feel very loved, thus giving us encouragement to keep living.